23. TWO RECURRENT CASES OF DERMATOFIBROSARCOMA PROTUBERANS: LESSONS IN DIAGNOSIS AND SURGICAL MANAGEMENT (Vietnam Journal of Community Medicine, 2025)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive cutaneous sarcoma that often mimics benign lesions, leading to delayed diagnosis and high recurrence risk. We present two diagnostically challenging cases. The first involved a 15-year-old girl with a painless nodule on the index finger. She underwent two resections without prior biopsy. An incisional biopsy suggested dermatofibroma, and two subsequent resections were performed. Recurrences led to index ray amputation. Final histopathology confirmed dermatofibrosarcoma protuberans with diffuse CD34 positivity. The second case involved a 51-year-old woman with a painful, pruritic nodule on the left thigh that recurred after excision and persisted for nine years. MRI showed a subcutaneous mass, and biopsy confirmed dermatofibrosarcoma protuberans. Wide local excision with 2-3 cm margins to the fascia was performed. Preoperative skin mapping and margin orientation enabled precise pathological assessment and allowed for targeted re-excision if needed. Skin undermining was avoided, and closure achieved with a skin graft. Both cases have shown no recurrence during follow-up and achieved acceptable functional outcomes. These cases emphasize the need for early biopsy and CD34 immunostaining in atypical or persistent skin lesions. Wide excision with accurate surgical margin assessment is critical for curative treatment and recurrence prevention.
Keywords: Dermatofibrosarcoma protuberans; soft tissue sarcoma; surgical margins; CD34; recurrence.